Finite Element Approach to Assess the Benefits of Asphalt Solar Collectors. Issue 1 (2016) - Dakessian, Lala; Harfoushian, Hagop; Habib, David; Chehab, Ghassan R.; Saad, George; Srour, Issam
Asphalt solar collectors (ASCs) consist of a pipe network embedded in the surface asphalt layer of an asphalt pavement. As fluid circulates in the pipes, it absorbs heat from the pavement and cools it down. While previous research has concentrated on studying ASC parameters independently, this study combined them in a comprehensive model to evaluate the potential of ASCs to harvest energy from pavements and mitigate the negative impact of their high surface temperatures. For that purpose, a finite element model of an ASC was developed to predict the temperature profile of the pavement, pipes, and circulating fluid. The model was validated under field conditions with two flow configurations: a closed loop system with reservoir and a single-pass system. The single-pass system was shown to yield a higher efficiency than a closed loop system would (21.9% versus 10.9%). Once validated, the model was used to simulate ASC water and pavement temperatures during representative days of four seasons for a specific climate. The finite element model predicted that a single-pass ASC would increase water temperatures by an average of 4.0°C, 7.5°C, 10.2°C, and 13.6°C and reduce pavement surface temperatures by an average of 0.5°C, 0.7°C, 2.5°C, and 3.2°C throughout the days in winter, autumn, spring, and summer, respectively. These reductions resulted in a 3-year extension of the pavement lifetime for a prescribed set of traffic, structural, climatic, and materials conditions. The potential energy gain and service life extension were used to conduct an economic analysis, which estimated a 5-year payback period of the ASC.